RAPID ASSESSMENT OF COASTAL ECOSYSTEM AND BIODIVERSITY IMPACTS DRIVEN BY SHRIMP AQUACULTURE IN NORTHERN JAVA - Muhammad Alriefqi Palgunadi; Achmad Fuad Fathurrahman; Muh Azril; Agus Jaenudin; Randy Alihusni Wardana; Yuni Setyaningsih (Lambung Mangkurat University-Indonesia, 2025)
Shrimp aquaculture has rapidly expanded along Indonesia’s northern Java coast, raising concerns about its ecological implications, particularly in traditional shrimp farming. This rapid assessment evaluates the environmental and biodiversity impacts of traditional shrimp farming in Brebes, Central Java, focusing on current ecosystem conditions and future implications through scenario-based analysis. This study conducted a rapid ecological assessment to evaluate the environmental and biodiversity impacts of long-established traditional shrimp ponds. A descriptive qualitative approach was used, combining ecological field surveys, spatial analysis, interviews, and scenario-based comparisons of “with farm” and “no farm” conditions. The assessment recorded 54 plant species and 50 fauna species, including 10 nationally protected fauna and the Vulnerable smooth-coated otter (Lutrogale perspicillata), which faces increasing conflict with farmers. Spatial analysis confirmed that shrimp ponds are located outside protected areas and critical habitats and were not constructed on converted mangrove or natural wetlands ecosystem. Scenario modelling comparing